2022
DOI: 10.3389/fpsyg.2022.857659
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Affects the Level of Psychological Distress in Patients With Lung Cancer via Illness Perception and Perceived Stress: A Cross-Sectional Survey Study

Abstract: PurposeThe aims of the study were first to investigate the association between illness perception and psychological distress and second to determine whether mindfulness affects psychological distress via illness perception and perceived stress in patients with lung cancer.MethodsAmong 300 patients with lung cancer who participated in this cross-sectional study, 295 patients made valid responses to distress thermometer (DT), the Five Facet Mindfulness Questionnaire (FFMQ), the Brief Illness Perception Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…This study also explored the relationship between illness perception and menopause symptoms in women with breast cancer undergoing chemotherapy. Illness perception is an important cognitive factor during treatment and is significantly associated with psychological symptoms and behaviors in women with cancer 46-48 . These findings emphasize the necessity of integrating these factors when developing interventions designed to improve the well-being and health of women with breast cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 93%
“…This study also explored the relationship between illness perception and menopause symptoms in women with breast cancer undergoing chemotherapy. Illness perception is an important cognitive factor during treatment and is significantly associated with psychological symptoms and behaviors in women with cancer 46-48 . These findings emphasize the necessity of integrating these factors when developing interventions designed to improve the well-being and health of women with breast cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 93%
“…Both mindfulness 89 and social support 90 are positive sources for copying with negative psychological states, and our previous studies have demonstrated the inverse association between mindfulness and social support and psychological distress. 15 , 56 , 58 In contrast, stigma, a negative emotional experience that includes isolation, rejection, degradation, and criticism due to undesirable conditions, 77 has been demonstrated to be a predictor of psychological distress in patients with lung cancer. 47 In general, psychosomatic balance plays a vital role in regulating the psychological well-being of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 54 , 55 In addition, our previous studies explicitly investigated the roles of social support, perceived stigma, perceived stress, coping styles, self-esteem, mindfulness, and illness perception in the development of psychological distress in patients with lung cancer. 15 , 56 , 57 , 58 However, it remains unclear which pathways may mediate the interventional effects of the MBSR program on psychological distress in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Higher illness perception scores correspond to negative views regarding how a patient’s illness impacts their health. 36 …”
Section: Methodsmentioning
confidence: 99%